Helmet Ventilation in a Child with COVID-19 and Acute Respiratory Distress Syndrome - Ke-Yun Chao; Chao-Yu Chen; Xiao-Ru Ji; Shu-Chi Mu; Yu-Hsuan Chien (Hindawi Limited, 2024)
Background. In pediatric patients with severe COVID-19, if the respiratory support provided using high-flow nasal cannula (HFNC) becomes insufficient, no definitive evidence exists to support the escalation to noninvasive ventilation (NIV) or mechanical ventilation (MV). Case Presentation. A 9-year-old boy being treated with face mask-delivered biphasic positive airway pressure ventilation developed fever, tachypnea, and frequent desaturation. The COVID-19 polymerase chain reaction test and urine antigen test for Streptococcus pneumoniae were both positive, and sputum culture yielded Pseudomonas aeruginosa. The do-not-resuscitate order precluded the use of endotracheal intubation. After 2 h of HFNC support, the respiratory rate oxygenation (ROX) index declined from 7.86 to 3.71, indicating impending HFNC failure. A helmet was used to deliver NIV, and SpO2 was maintained at >90%. Dyspnea and desaturation gradually improved, and the patient was switched to HFNC 6 days later and discharged 10 days later. Conclusion. In some cases, acute respiratory distress syndrome severity cannot be measured using the oxygenation index or oxygenation saturation index, and the SpO2/FiO2 ratio and ROX index may serve as useful alternatives. Although NIV delivered through a facemask or HFNC is more popular than helmet-delivered NIV, in certain circumstances, it can help escalate respiratory support while providing adequate protection to healthcare professionals.